2011
DOI: 10.1038/emboj.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

APP and APLP2 are essential at PNS and CNS synapses for transmission, spatial learning and LTP

Abstract: Despite its key role in Alzheimer pathogenesis, the physiological function(s) of the amyloid precursor protein (APP) and its proteolytic fragments are still poorly understood. Previously, we generated APPsa knock-in (KI) mice expressing solely the secreted ectodomain APPsa. Here, we generated double mutants (APPsa-DM) by crossing APPsa-KI mice onto an APLP2-deficient background and show that APPsa rescues the postnatal lethality of the majority of APP/APLP2 double knockout mice. Surviving APPsa-DM mice exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 44 publications
(59 reference statements)
1
69
0
1
Order By: Relevance
“…Interestingly, the decrease in pTau levels parallels with a significant increase in the inactive form of glycogen synthase kinase-3β (GSK3β) (GSK3β phosphorylated at Ser9; Figure 4c), one of the main kinases involved in the pathogenic mechanisms of AD through the phosphorylation at multiple sites of tau (Mandelkow et al, 1992). As a decrease in APP may result detrimental for its contribution to synaptic plasticity and hippocampus-dependent memory (Goguel et al, 2011;Weyer et al, 2011), we analyzed the effect of CM-414 on APP in WT mice. As depicted in Supplementary Figure S6a, we demonstrated that CM-414 did not affect APP or C99 levels in WT mice after 5 days of treatment, whereas the same treatment significantly reduced the levels of both APP and C99 and Aβ 40 in Tg2576 mice (Supplementary Figure S6b).…”
Section: Effects Of Cm-414 On Pathological Markers Of Ad In Aged-tg25mentioning
confidence: 99%
“…Interestingly, the decrease in pTau levels parallels with a significant increase in the inactive form of glycogen synthase kinase-3β (GSK3β) (GSK3β phosphorylated at Ser9; Figure 4c), one of the main kinases involved in the pathogenic mechanisms of AD through the phosphorylation at multiple sites of tau (Mandelkow et al, 1992). As a decrease in APP may result detrimental for its contribution to synaptic plasticity and hippocampus-dependent memory (Goguel et al, 2011;Weyer et al, 2011), we analyzed the effect of CM-414 on APP in WT mice. As depicted in Supplementary Figure S6a, we demonstrated that CM-414 did not affect APP or C99 levels in WT mice after 5 days of treatment, whereas the same treatment significantly reduced the levels of both APP and C99 and Aβ 40 in Tg2576 mice (Supplementary Figure S6b).…”
Section: Effects Of Cm-414 On Pathological Markers Of Ad In Aged-tg25mentioning
confidence: 99%
“…Notably, however, APP was recently shown to be required for maintenance of distal synaptic connections in APP/APLP2 knockout mice. 119 Hence, the increase in APP synthesis-so far exclusively considered as a trigger of accelerated production of 'neuro toxic' Aβ peptides-may be a physiological reaction of neurons to ensure stabilization of their synapses under stress conditions.…”
Section: Inflammation and Cellular Stressmentioning
confidence: 99%
“…Indeed, in a transgenic mouse model of AD, dystrophic axons associated with Aβ plaques remained continuous and connected to viable neuronal somata. 129 Nevertheless, the lack of stabilizing presynaptic proteins, including APP, 119 is expected to trigger synaptic disconnectiona well-described feature of early-stage AD pathophysiology. 130 Secondary impairments in mitochondrial transport and energy supply, 131 and aberrant maturation of autophagic vacuoles, 30 are likely to further promote axonal de generation and induce neuronal death.…”
Section: From Varicosities To Degenerationmentioning
confidence: 99%
“…This indicates that the gene trap alleles do not completely disrupt normal splicing of the gene and are not null alleles. Moreover, the production of soluble Appa-RFP and Aplp2-RFP fusion proteins may compensate for the loss of the full-length Appa and Aplp2 proteins, similar to studies in mice (Weyer et al, 2011). The ligand binding and adhesive activity of the extracellular domain of APP is important for its role in synaptogenesis, cell adhesion, and neurite outgrowth, but the exact biological function remains unclear (Jacobsen and Iverfeldt, 2009).…”
Section: Appa-rfp and Aplp2-rfp Are Localized To Blood Vessels In Thementioning
confidence: 90%
“…In addition, the sAPP peptide is sufficient to rescue molting and morphogenesis defects from loss of APL-1 in Caenorhabditis elegans and is suggested to function in a cell-nonautonomous manner (Hornsten et al, 2007). In mice, a knock-in allele that produces sAPPα exclusively rescues the postnatal lethality in APP/APLP2 double mutants (Weyer et al, 2011), suggesting that much of the normal biological function of the APP gene family can be mediated through the soluble extracellular domains. It is also intriguing that patients with AD display reduced levels of the sAPPα cleavage peptide (Lannfelt et al, 1995), raising the possibility that the sAPPα could contribute to the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%